Sciatic Herpes Zoster Suspected of Lumbar Disc Herniation: An Infrequent Case Report and Literature Review - Wei, Fei-Long; Li, Tian; Song, Yang; Bai, Lin-Ya; Yuan, Yifang; Zhou, Chengpei; Qian, Jixian; Yan, Xiaodong (Frontiers in Surgery, 2021)
Abstract Background: The symptoms of sciatic herpes zoster are sometimes difficult to distinguish from sciatica caused by lumbar disc herniation. We describe a case of suspected lumbar disc herniation with sciatic herpes zoster to reduce the rate of misdiagnosis. Case Report: A 55-year old man, male, developed low back pain after carrying heavy items 20 years ago. Characteristics of symptoms: 1. Symptoms were aggravated in the upright lumbar forward flexion position; 2. The VAS (leg) score was 8-9 points and the VSA (lumbar) score was 0 point; 3. It can be relieved when rested in the supine position; 4. It came on intermittently with radiation pain in the right lower limb. There were several attacks every year. One month ago, there was radiating pain in the right lower limb. The pain was from the back of the right hip, behind the thigh, in lateral crural region, to the back of the foot. And Symptoms worsened for 10 days. The VAS score was 8 points. Pain could not be relieved by rest or changing posture. There was no back pain, no lower limbs, weak walking, no claudication and other symptoms. Analgesics and neurotrophic drugs are ineffective. After the application of antiviral drugs, the radiation pain in the right lower extremity was significantly relieved. Conclusion: We describe this case in detail and discuss how to make an authentic diagnosis, with a concomitant literature review.